Administration Timing and Efficacy of Tocilizumab in Patients With COVID-19 and Elevated IL-6 - Li, Pan; Lu, Zhengmao; Li, Qiang; Wang, Zhenmeng; Guo, Yan; Cai, Chen; Wang, Shengyun; Liu, Peng; Su, Xiaoping; Huang, Yi; Dong, Yuchao; Qiu, Wenjuan; et al. (Frontiers in Molecular Biosciences, 2021)
Background Tocilizumab (TCZ), an interleukin-6 receptor antibody, has previously been used for treating patients with the coronavirus disease 2019 (COVID-19), but there is a lack of data regarding the administration timing of TCZ. Objectives This study aimed to evaluate the timing and efficacy of TCZ in the treatment of patients with COVID-19. Methods Laboratory-confirmed patients with COVID-19 with an elevated interleukin-6 (IL-6) level (>10 pg/ml) were offered TCZ intravenously for compassionate use. Clinical characteristics, laboratory tests, and chest imaging before and after the administration of TCZ were retrospectively analyzed. Results A total of 58 consecutive patients who met the inclusion criteria and with no compliance to the exclusion criteria were included. Of these 58 patients, 39 patients received TCZ treatment, and 19 patients who declined TCZ treatment were used as the control cohort. In the TCZ-treatment group, 6 patients (15.4%) were in mild condition, 16 (41.0%) were in severe condition, and 17 (43.6%) were in critical condition. After TCZ treatment, the condition of 27 patients (69.2%) improved and 12 (30.8%) died. Compared with the improvement group, patients in the death group had higher baseline levels of IL-6 (P = 0.0191) and procalcitonin (PCT) (P = 0.0003) and lower lymphocyte percentage (LYM) (P = 0.0059). Patients receiving TCZ treatment had better prognoses than those without TCZ treatment (P = 0.0273). Furthermore, patients with a baseline IL-6 level of ≥100 pg/ml in the TCZ-treatment group had poorer clinical outcomes than those with an IL-6 level of <100 pg/ml (P = 0.0051). Conclusion The administration of TCZ in an early stage of cytokine storm (IL-6 level < 100 pg/ml) may effectively improve the clinical prognosis of patients with COVID-19 by blocking the IL-6 signal pathway.